The Ruby Slippers Across Time, Space and Media (Imaginations: Journal of Cross-Cultural Image Studies, 2018)
This article discusses representations of Dorothy’s magical shoes in diverse media—from the original text by L. Frank Baum (1900) to the classic MGM film (1939) to Vogue’s 2005 fashion shoot by Annie Leibovitz. According to Salman Rushdie, “the real secret of the ruby slippers is not that ‘there’s no place like home’, but rather that there is no longer any such place as home.” Canadian designer John Fluevog shares this point of view, as exemplified most prominently by The Cosmos: Meteor shoes (2016), which celebrate the road as the destination itself. I compare Fluevog to Gucci’s flamboyant Star Trek-inspired campaign GucciandBeyond (2017), as well as the brand’s more recent Utopian Fantasy campaign (2018). The essay cites, among others, Alain de Botton and Andy Warhol, both professing their fascination with air travel. Additional critical sources include Dick Hebdige’s pioneering work on style subcultures, and MOMA’s recent volume on Fashion Is. The essay’s concluding sections discusses commercial appropriation of fashion, as well as fashion’s open-ended definition.